Adaptive enhancement of learning protocol in hippocampal cultured networks grown on multielectrode arrays - Pimashkin, Alexey; Gladkov, Arseniy; Mukhina, Irina; Kazantsev, Victor (Frontiers in Neural Circuits, 2013)
Learning in neuronal networks can be investigated using dissociated cultures on multielectrode arrays supplied with appropriate closed-loop stimulation. It was shown in previous studies that weakly respondent neurons on the electrodes can be trained to increase their evoked spiking rate within predefined time window after the stimulus. Such neurons can be associated with weak synaptic connections in nearby culture network. The stimulation leads to the increase in the connectivity and in the response. However, it was not possible to perform the learning protocol for the neurons on electrodes with relatively strong synaptic inputs and responding at higher rates. We proposed an adaptive closed-loop stimulation protocol capable to achieve learning even for the highly respondent electrodes. It means that the culture network can reorganize appropriately its synaptic connectivity to generate a desired response. We introduced an adaptive reinforcement condition accounted for response variability in control stimulation. It significantly enhanced the learning protocol to many responding electrode independently on its base response level. We also found that learning effect preserved after 4-6 hours after training.